Islam: a new history from Muhammad to the present - Tolan, John Victor (Princeton University Press, 2025)
Cover -- Contents -- Acknowledgments -- Introduction -- Part I. Foundations -- Chapter 1. The Quran and the Birth of a Community of Believers -- Chapter 2. The Umayyad Dynasty and the Birth of an Imperial Religion -- Chapter 3. Abbasid Baghdad: Crucible of a Multiconfessional Civilization -- Chapter 4. The Three Caliphates of the Year 1000 -- Part II. Expansion -- Chapter 5. Invasions and Reconfigurations of the Muslim World, Eleventh-Thirteenth Centuries -- Chapter 6. The World of Ibn Battuta -- Chapter 7. Muslim Empires (Fourteenth-Seventeenth Centuries) -- Part III. Modernities -- Chapter 8. Colonization and Its Discontents, 1798-1918 -- Chapter 9. Decolonization, Nationalism, and the Emergence of Political Islam in the Twentieth Century -- Chapter 10. Between Reform and Radicalism: Being Muslim in the Twenty-First Century -- Notes -- Selected Bibliography -- Index.